2014
DOI: 10.1186/1472-6750-14-83
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting polyhydroxybutyrate accumulation in mesophyll cells of sugarcane and switchgrass

Abstract: BackgroundPolyhydroxyalkanoates are linear biodegradable polyesters produced by bacteria as a carbon store and used to produce a range of bioplastics. Widespread polyhydroxyalkanoate production in C4 crops would decrease petroleum dependency by producing a renewable supply of biodegradable plastics along with residual biomass that could be converted into biofuels or energy. Increasing yields to commercial levels in biomass crops however remains a challenge. Previously, lower accumulation levels of the short si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The PHAs constitute, among natural polymers, the largest group of microbial polyesters that displays thermoplastic features (9, 13) (hence the commonly used term "bioplastics"). They have been hailed as potential competitors of oil-derived plastics, not only because of their physical properties but also for their biocompatibility and biodegradability (8,14,15) and the high sustainability of their sources, as they naturally accumulate as a reserve material in several microbial (16) and engineered plant (17) species. The tunable structural features of these polyesters based on their variable compositions make them highly attractive for the development of next-generation biomaterials capable of being functionalized with peptides and proteins.…”
Section: Importancementioning
confidence: 99%
“…The PHAs constitute, among natural polymers, the largest group of microbial polyesters that displays thermoplastic features (9, 13) (hence the commonly used term "bioplastics"). They have been hailed as potential competitors of oil-derived plastics, not only because of their physical properties but also for their biocompatibility and biodegradability (8,14,15) and the high sustainability of their sources, as they naturally accumulate as a reserve material in several microbial (16) and engineered plant (17) species. The tunable structural features of these polyesters based on their variable compositions make them highly attractive for the development of next-generation biomaterials capable of being functionalized with peptides and proteins.…”
Section: Importancementioning
confidence: 99%
“…We further interrogated the model to see whether metabolic impairment can be due to the compartmentalization of PHB synthesis, which mainly occurs in BS chloroplasts (McQualter et al, 2014b;Petrasovits et al, 2012). Figure 5c shows that the relative ATP demand in BS increased at increasing r CD but only when PHB synthesis was compartmentalized to M. When PHB synthesis was all compartmentalized to BS (V DBS /V D = 1) ATP demand in BS decreased for increasing r CD reflecting the ATP advantage of pyruvate decarboxylation in BS.…”
Section: Metabolic Modellingmentioning
confidence: 99%
“…Strategies to increase PHB production in plants have relied initially on determining the most suitable subcellular compartment for expression of the PHB pathway (Nawrath et al, 1994;Petrasovits et al, 2007), with sufficient enzyme activity to maximize use of available substrate (Bohmert-Tatarev et al, 2011;Petrasovits et al, 2012;Somleva et al, 2008). Access to substrate in M was found to be problematic in C 4 grasses (McQualter et al, 2014b;Petrasovits et al, 2013) and remedied by the use of an acetoacetyl-CoA synthase in place of a b-ketothiolase (McQualter et al, 2014a). Increasing A by adjusting flux through the RPP cycle (Somleva et al, 2013) significantly corrected adverse phenotypes and increased PHB production in switchgrass plants.…”
Section: Improvement Of Phb Production In Sugarcanementioning
confidence: 99%
“…We previously demonstrated that chemical inhibition of acetyl‐CoA carboxylase (ACCase), the enzyme that commits carbon to FAS, substantially increased PHB accumulation (Petrasovits et al ., ). We also showed that ACCase inhibition leads to a considerable increase in polymer production in M cells (McQualter et al ., ), suggesting that access to substrate limits PHB production in M cells. In an attempt to better utilize the capacity of M cells for PHB synthesis, we have explored a strategy to access the available substrate(s) more effectively using the recently described novel acetoacetyl‐CoA synthase (AACS) encoded by the nphT7 gene of Streptomyces sp.…”
Section: Introductionmentioning
confidence: 97%